Islamic Astronomy of Abbasid Era (750-1258 AD) - Aziz, Muhammad Ilham; Musta'id, Ahmad (Institute of Research and Community Service UIN Prof. K.H. Saifuddin Zuhri, 2022)
Astronomy is a particular field in Islam related to the interests of daily Muslim worship practices, such as determining the beginning of prayer times, qibla direction, and the beginning of the Qamariyah month. During the Abbasid period 750-1258 AD, especially during the reign of Abu Ja'far Al-Mansur, Harun Al-Rashid, and Al-Ma'mun, Islamic astronomy developed significantly. This can be seen from the emergence of astronomers. The love of the three Abbasid caliphs for science significantly influenced the policies related to development in science. The method used in this study is a qualitative method with historical analysis techniques. This study aims to add to the enrichment of historical treasures related to the development of science, especially astronomy, during the Abbasid period. Meanwhile, astronomy during the Abbasid period also had many scientific sources that needed to be studied more comprehensively. That is, many scientific figures in astronomy have never been specifically studied. Therefore, the study of astronomy today in higher education must also seriously focus on learning classical knowledge. This paper discusses the Abbasid state in developing science during its reign by looking at it from the perspective of significant scientific developments during the leadership of its caliph, which was indirectly influenced by socio-religious and intellectual conditions in his time. During the Abbasid era, the progress of science had reached its golden age, especially in Islamic astronomy which had contributed to the development of its science in the field of astronomy in the period after that until now.